막과산화를 신속히 유발하는 제초제의 고효율 대량스크리닝을 위한 형광검정법 - 김진석(Jin-Seog Kim); 권옥경(Ok Kyung Kwon) (Weed & turfgrass science, 2015)
This study was conducted to establish a fluorescence assay system for high efficient mass screening of the herbicides causing rapid membrane peroxidation, based on the fact that peroxide in cellular leakage could be fluorometrically determined through the fuorescent compounds formed after reacting with homovanillic acid (HVA) and peroxidase (HRP). The assay procesure established in this study was as follows. Only single disc (4 mm diameter) excised from cucumber cotyledon is placed on the well containing test solution ($200μL$) with 96-well microplate. The plate is shaking-incubated for 8 h under light condition. Then after removing the cucumber disc, HVA and HRP are supplied in the medium buffer and incubated for 5 min at room temperature. Fluorescence values are determined at Ex 320 nm/Ex 425 nm. The higher fluorescence values are obtained in the treatment of chemical having higher herbicidal activity. Using this assay with 96-well microplates, a large number of herbicides inducing rapid membrane peroxidation seemed to be screened more efficiently than spectrophotometric microtiter assay reported previously. 본 연구는 식물세포막을 파괴시켜 제초활성을 나타내게 하는 화합물(막과산화형 제초제)을 미지의 많은 화합물로부터 신속하게 탐색하기 위한 새로운 검정법을 확립하기 위하여 실시되었으며, 확립한 전체적인 검정과정은 다음과 같다. 96-well microplate에 시험용액 $200μL$ 넣고 여기에 오이자엽으로부터 적출한 직경 4 mm의 절편 1개씩을 띄운다. 항온실의 광조건 하에서 회전진탕기로 조금씩 흔들어주면서 8시간 배양한 후 절편을 제거한 다음, 배양액에 HVA와 HRP를 첨가하여 반응시킨 후 마이크로평판용 형광검출기를 이용하여 형광도(Ex 320 nm, Em 425 nm)를 측정한다. 형광변화량이 높을수록 제초활성이 높은 것으로 판단한다. 본 방법은 96-well microplate에서 작업을 수행할 수 있고 형광검출 기술을 이용함으로써 검정과정과 작업을 간편하게 하여 검정효율을 기존보다 현저히 높인 것이 특징이다. 아울러 활성검정을 추출된 효소가 아닌 잎 절편수준에서 수행하기 때문에 보다 실용화에 근접한 정량적 데이터를 얻을 수 있는 장점을 가진다.